Financial Factors Affecting on Foreign Direct Investment Flows into Nepal (Researcher CAB: A Journal for Research and Development, 2023)
Foreign direct investment in Nepal has played a vital role in bridging the gap between demand for capital and supply of capital in the country as it has been facing scarcity of capital supply. The main objective of this study is to examine the role of financial variables on foreign direct investment flows into Nepal. Regression analysis and elasticity coefficient are used to examine the role of financial sector in foreign direct investment flows. The result shows that the coefficient of broad money supply (0.81), NEPSE index (-0.71) and total transaction in financial market (0.38) are the significant variables affecting foreign capital flows into Nepal. However, NEPSE index negatively affects foreign capital flows into Nepal. Since the Government of Nepal has undertaken various measures to raise FDI flows into the country, the government should carefully develop the financial sector as it is one of the prominent factors affecting the foreign capital flows.